Robust Control of a Wind Turbine Using Third Generation CRONE Control - Ravasco, Francisco (2020)
This paper presents the identification, development and simulation of a complex order, third generation CRONE controller for a new vertical-axis wind turbine prototype of the Darrieus type. The prototype was tested in a wind tunnel and the data used to develop an accurate model, validated experimentally. The CRONE control system design methodology was then used to develop a robust controller, which was then tested in simulation. Simulations allow for parameter uncertainty and different wind conditions, with and without the presence of turbulence. This control system can be easily implemented using an Arduino platform.